A 2 Bill or Two 1 Bills: An Experiment that Challenges Standard Protocol. Issue 3 (August 2019) - Mills, Sarah
The 2 bill is commonly used as a prepaid incentive in survey administration. Despite the widespread use of this incentive, there is no peer-reviewed research into how providing a single 2 bill rather than two 1 bills affects survey response rate. The results are from a mail survey of 2, 970 rural landowners in Michigan with identical survey protocols. Half were randomly assigned to receive a single 2 bill and the other half to receive two 1 bills accompanying the questionnaire. I found no statistical difference in the response rates of the two groups. While there may be logistical advantages to using a single 2 bill compared to two 1 bills, this research suggests that the 2 bill is not more effective at inducing survey participation.